S50 Monocytes from IPF patients show pre-conditioned pro-repair features. (15th November 2016) - Fraser, E; Blirando, K; St.Noble, V; Benamore, R; Hoyles, R; Benlahrech, A; Ho, LP
Abstract : Introduction: The central mechanism in IPF is a dysfunctional alveolar epithelial-fibroblast interaction resulting in an aberrant repair process. This defect is influenced by other immune processes; one of these is the macrophage pathway. Macrophages are heterogeneous immune cells that can control all phases of the repair process. 'M2' or 'reparative' macrophages have anti inflammatory and reparative phenotype, with high scavenger activities. We investigate how monocytes (precursors of monocyte-derived lung macrophages) might contribute to fibrogenesis in IPF. Methods: 35 IPF patients (25 sampled while stable and 10 with AE-IPF) diagnosed according to the 2011 ATS/ERS/JRS/ALAT guidelines, with 'definite' or 'probable' IPF and age and gender-matched healthy controls were recruited over a one-year period. Those with emphysema greater than 25%, current smokers and malignancy were excluded. Lung function and CT fibrosis score1 were performed. Phenotype and function of purified monocytes and monocyte-derived macrophages (MDMs) were determined using qPCR and multi-flow cytometry for selected M1 and M2 genes and proteins (M1 – CD64 M2 – CD163 and CD200R by FACS; and 26 M1 and M2 macrophage markers against three house keeping genes). The ability of MDMs to phagocytose (using pHrodo method) and ROS content (using H2DCFDA assays) ex vivo were also examined. Results and discussion: Circulating monocyte levels were significantly higher in IPF compared to healthy controls (p < 0.001) and correlated negatively with lung function (FVC r = −0.6, p = 0.003) and CT fibrosis score (r = 0.45, p = 0.007). IPF monocytes displayed higher M2:M1 ratio profile compared to healthy controls – with higher IL10, CD163, IL1R2, FGL2 and lower TNFa and CXCL10 gene expression. When these monocytes were differentiated to macrophages (MDMs) ex vivo, IPF macrophages showed a significantly higher level of M2 markers and CD14 expression, reduced phagocytosis and produce lower levels of ROS –supporting M2 and pro-repair phenotype. Conclusions: Our data show that circulating monocytes in IPF are elevated compared to age-matched controls, correlate positively with disease severity, and are different from those found in age-matched healthy controls. They have pro-repair, M2-like features and differentiate to pro-repair monocyte-derived macrophages and may contribute to the aberrant repair process in IPF. Reference: Best AC, et al . Idiopathic pulmonary fibrosis: physiologic tests, quantitative CT indexes, and CT visual scores as predictors of mortality. Radiology 2008; 246 :935–40.